Autohoodening: The Rise of Captain Swing - Kargotis, Demetrios; Mortimer, Nicholas; Macdonald, Dash (My University, 2022)
Autohoodening is a collaborative performance work that reimagines the historic Kentish midwinter custom of Hoodening through the lens of contemporary labour conditions and automation. Developed as part of the wider Autohoodening Symposium (2019–), the project draws on archival research, worker testimonies, and trade union perspectives to create a tragicomic operatic film. Rooted in the carnivalesque traditions of East Kent farm labourers, the work translates the symbolic horse effigy and seasonal ritual into a critique of modern logistics systems, particularly focusing on the working realities within Amazon fulfilment centres. Through song, satire, and embodied performance, Autohoodening interrogates the hidden infrastructures of convenience capitalism and the human cost behind “one-click” consumption.
Keywords: Film opera; Activism; Amazon; Costume; Folk history; Reimagining; Singing; Captain Swing; Post Workers Theatre